Impact of obesity on the toxicity of a multi-ingredient dietary supplement, OxyELITE Pro™ (New Formula), using the novel NZO/HILtJ obese mouse model: Physiological and mechanistic assessments. (December 2018) - Skinner, Charles M.; Miousse, Isabelle R.; Ewing, Laura E.; Sridharan, Vijayalakshmi; Cao, Maohua; Lin, Haixia; Williams, D. Keith; Avula, Bharathi; Haider, Saqlain; Chittiboyina, Amar G.; Khan, Ikhlas A.; ElSohly, Mahmoud A.; et al.
Abstract: Herbal dietary supplement (HDS)-induced hepato- and cardiotoxicity is an emerging clinical problem. In this study, we investigated the liver and heart toxicity of HDS OxyELITE-PRO™ New Formula (OEP-NF), a dietary supplement marketed for weight loss and performance enhancement that was recently withdrawn from the market. Using a novel NZO/HlLtJ obese mouse model, we demonstrated that administration of clinically relevant mouse equivalent doses (MED) of OEP-NF produced cardio- and hepatotoxic risks following both short- and long-term administration schedules. Specifically, gavaging female NZO/HlLtJ with up to 2X MED of OEP-NF resulted in 40% mortality within two weeks. Feeding mice with either 1X or 3X MED of OEP-NF for eight weeks, while not exhibiting significant effects on body weights, significantly altered hepatic gene expression, increased the number of apoptotic and mast cells in the heart and affected cardiac function. The degree of toxicity in NZO/HlLtJ mice was higher than that observed previously in non-obese CD-1 and B6C3F1 strains, suggesting that an overweight/obese condition can sensitize mice to OEP-NF. Adverse health effects linked to OEP-NF, together with a number of other hepato- and cardiotoxicity cases associated with HDS ingestion, argue strongly for introduction of quality standards and pre-marketing safety assessments for multi-ingredient HDS. Highlights: Dietary supplement OxyELITE Pro™ - New Formula (OEP-NF) was linked to severe liver injuries in the United States. Toxicity of OEP-NF was assessed using a novel NZO/HlLtJ obese mouse model. OEP-NF produced histological, biochemical and molecular alterations that are characteristic to liver and cardiac injury. OEPNFinduced weight loss was transitory, followed by body weight gain in all experimental groups. These findings bolster concerns for the safety and efficacy of OEP-NF, and similar products, in humans.